On Determining The Conditions For Effective Operation Of The Vacuum Valve Of Cotton Separators - Akramjanov Dilmurod Muxtor o’g’li; Boltabayev Bekzod Egamberdiyevich; Khusanov Sadi Makhamatjonovich; Muradov Rustam Muradovich (The American Journal of Engineering and Technology, 2020)
The article analyzes the efficiency results for the improvement and production of the separator device of the vacuum valve of the separator, the dependence of the number of revolutions of the network drum on changes in cotton pollution and the dependence